2d-3+3c-2d-3+3c=4d-12+6c

Simple and best practice solution for 2d-3+3c-2d-3+3c=4d-12+6c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2d-3+3c-2d-3+3c=4d-12+6c equation:


Simplifying
2d + -3 + 3c + -2d + -3 + 3c = 4d + -12 + 6c

Reorder the terms:
-3 + -3 + 3c + 3c + 2d + -2d = 4d + -12 + 6c

Combine like terms: -3 + -3 = -6
-6 + 3c + 3c + 2d + -2d = 4d + -12 + 6c

Combine like terms: 3c + 3c = 6c
-6 + 6c + 2d + -2d = 4d + -12 + 6c

Combine like terms: 2d + -2d = 0
-6 + 6c + 0 = 4d + -12 + 6c
-6 + 6c = 4d + -12 + 6c

Reorder the terms:
-6 + 6c = -12 + 6c + 4d

Add '-6c' to each side of the equation.
-6 + 6c + -6c = -12 + 6c + -6c + 4d

Combine like terms: 6c + -6c = 0
-6 + 0 = -12 + 6c + -6c + 4d
-6 = -12 + 6c + -6c + 4d

Combine like terms: 6c + -6c = 0
-6 = -12 + 0 + 4d
-6 = -12 + 4d

Solving
-6 = -12 + 4d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-4d' to each side of the equation.
-6 + -4d = -12 + 4d + -4d

Combine like terms: 4d + -4d = 0
-6 + -4d = -12 + 0
-6 + -4d = -12

Add '6' to each side of the equation.
-6 + 6 + -4d = -12 + 6

Combine like terms: -6 + 6 = 0
0 + -4d = -12 + 6
-4d = -12 + 6

Combine like terms: -12 + 6 = -6
-4d = -6

Divide each side by '-4'.
d = 1.5

Simplifying
d = 1.5

See similar equations:

| -x-16=-5x | | y=-2.7x^2+30x+6.5 | | 93.96=4.7p+8.79p-2.6p | | 3(x+2)=9x+1-6x+5 | | -4(-5x-4)=-44 | | x-.3x=200 | | 5.1-x=20.3 | | .25(-8x+8)=-2+2x | | x^2-13x*y+40y^2=0 | | 2(7d-6)+8= | | lx+2l=-lx-2l | | 50-10(4-2)+6= | | 0.56x-0.86=11.35-2.74x | | -5x+12=-3x-6 | | .25(-8x-8x)=-2+2x | | 4(x+6)=3x-2 | | 5x+12=-3x-6 | | -7(x+4)-45=5-22 | | -14+x=x+29 | | 3y=3(6.68)-3 | | .25(-x+8)=-2+2x | | 12=5y-25 | | 7n+14=-2n+50 | | 8a+5c=3369 | | 6x-1-3=4 | | 0.5+0.25=2.00 | | Ln(x+3)+Ln(2)=Ln(16) | | ln(30x)=y | | lx+2l+lx-2l=0 | | 1/2x+6=1/6 | | 98=m-(-78) | | 3(x+6)=7x-10x+1 |

Equations solver categories